Outcomes of acute myeloid leukemia with myelodysplasia related changes depend on diagnostic criteria and therapy. Issue 6 (20th March 2020) - Montalban‐Bravo, Guillermo; Kanagal‐Shamanna, Rashmi; Class, Caleb A.; Sasaki, Koji; Ravandi, Farhad; Cortes, Jorge E.; Daver, Naval; Takahashi, Koichi; Short, Nicholas J.; DiNardo, Courtney D.; Jabbour, Elias; Borthakur, Gautam; et al.
Abstract: Acute myeloid leukemia with myelodysplasia‐related changes (AML‐MRC) is a heterogeneous disorder defined by multilineage dysplasia, myelodysplastic syndrome (MDS)‐related karyotype, or history of prior MDS. We evaluated 415 patients with AML‐MRC treated from 2013 to 2018 and analyzed their clinical outcomes based on the diagnostic criteria of AML‐MRC, therapy type and mutation profile. Criteria for AML‐MRC included: cytogenetic abnormalities (AML‐MRC‐C) in 243 (59%), prior history of MDS in 75 (18%) including 47 (11%) with previously untreated MDS (AML‐MRC‐H) and 28 (7%) with previously treated MDS (AML‐MRC‐TS), and 97 (23%) with multilineage dysplasia (AML‐MRC‐M). Median age was 70 years (range 18‐94). Among 95 evaluable patients, a total of 37 (39%) had secondary‐type ( ASXL1, BCOR, EZH2, SF3B1, SRSF2, STAG2, U2AF1, ZRSR2 ) mutations. Mutations in ASXL1, BCOR, SF3B1, SRSF2, and U2AF1 tended to appear in dominant clones. By multivariate analysis, AML‐MRC subtype, age and serum LDH levels were independent predictors of outcome, with patients with AML‐MRC‐M (HR 0.56, CI 0.38‐0.84, P = .004) and AML‐MRC‐H having better OS. Compared to a cohort of 468 patients with AML without MRC, patients with AML‐MRC‐M/AML‐MRC‐H had similar outcomes to those with intermediate risk AML by European LeukemiaNet criteria. Intensive therapy was associated with improved OS in patients with AML‐MRC‐M (HR 0.42, CI 0.19‐0.94, P = .036) and with improved EFS in AML‐MRC‐M and AML‐MRC‐H (HR 0.26, CI 0.10‐0.63, P = .003). This data suggests that not all diagnostic criteria for AML‐MRC define high‐risk patients and that specific subgroups may benefit from different therapeutic interventions.